2006
DOI: 10.1088/0953-8984/18/34/004
|View full text |Cite
|
Sign up to set email alerts
|

A combined study of the magnetic properties of GdCrO4

Abstract: We have performed a detailed study of the magnetic properties of GdCrO 4 at low temperatures by complementary use of different macroscopic and microscopic physical techniques. A ferromagnetic order is established in this oxide below T C = 22 K. The ordered magnetic moments of the Cr 5+ ions are located along the crystallographic c-axis, forming an angle of ≈24• with the ordered moments of the Gd 3+ ions. Surprisingly, only 20% of the Gd 3+ sublattice orders at the Curie temperature of 22 K, while the remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
(33 reference statements)
2
12
0
Order By: Relevance
“…The magnetization curves are consistent with the reported data of M T (B) [23] and with the heat capacity C p,B (Sec. IV B) that show a ferromagnetic transition with a Curie temperature T C = 21.3 K, but present some unusual features, different than in a typical ferromagnet.…”
Section: Isothermal Magnetizationsupporting
confidence: 91%
See 3 more Smart Citations
“…The magnetization curves are consistent with the reported data of M T (B) [23] and with the heat capacity C p,B (Sec. IV B) that show a ferromagnetic transition with a Curie temperature T C = 21.3 K, but present some unusual features, different than in a typical ferromagnet.…”
Section: Isothermal Magnetizationsupporting
confidence: 91%
“…This interaction would also act on the Cr sublattice raising T C , which increases from 9.1 K for YCrO 4 to 21.3 K for GdCrO 4 . This also explains the low moment at the Gd sublattice observed by Mössbauer spectroscopy just below T C , at zero field [23].…”
Section: Isothermal Magnetizationsupporting
confidence: 54%
See 2 more Smart Citations
“…6,7 Many studies have been reported concerning the crystallographic, magnetic, and optical properties of phosphates, arsenates, and vanadates. 8,9 By contrast the RCrO 4 oxides have been much less studied because it is rather difficult to prepare them as pure phases, mainly due to the difficult to achieve the stabilization of the unusual Cr 5+ oxidation state 10,11 and the high tendency to be reduced to Cr 3+ giving the very stable RCrO 3 distorted perovskite phases.…”
Section: Introductionmentioning
confidence: 99%